Functional communication ability in frontotemporal lobar degeneration and Alzheimer’s disease - Isabel Albuquerque M. de Carvalho (Dementia & Neuropsychologia, 2008)
Functional communication is crucial for independent and efficient communicative behavior in re-sponse to every day activities. In the course of dementia progression, cognitive losses may impair these abilities. For this reason, functional communication assessment should be part of a formal assessment to quantify and qualify the impact of deficiency on patients’ lives. Objective: To compare functional communication abilities in fronto-temporal lobar degeneration (FLTD) and Alzheimer’s disease (AD). Methods: Six AD patients (mean age: 82.50±2.66 years; mean education: 5.67±3.61 years), and eight FTLD patients (mean age: 57.13±9.63 years; mean education: 10.86±6.91 years) had their close relatives answer the Functional Assessment of Communication Skills for Adults (Asha-facs) . Statistical analyses correlated the performance on each of the Asha-facs domains (social communication, communication of basic needs; reading, writing, number concept and daily planning) between both groups. Results: Analyses showed that functional communication was similar for AD and FTLD patients. Only two items had statistical difference, namely ‘Comprehension of inference’ (AD 6.7±1.33; FTLD 2.43±2.30, p=0.017) and ‘capacity to make basic money transactions’ (AD 2.17±2.04; FTLD 4.00±0.90, p=0.044). Comparison among the four domains’ mean scores revealed no significant difference. Conclusion: The Asha-facs is a useful instrument to characterize functional communication abilities in both FTLD and AD. Nevertheless, the analysis presented for this sample showed that the Asha-facs could not discriminate which aspects of the FTLD and AD differed.